Karakteristik Frozen-thawed Spermatozoa Domba Garut yang Dikriopreservasi dalam Pengencer yang Mendapat Imbuhan Orvus ES Paste (THE CHARACTERISTIC OF FROZEN-THAWED GARUT RAM SPERMATOZOA CRYOPRESERVED IN EXTENDER SUPPLEMENTED WITH ORVUS ES PASTE) - Hartanti, Andhani Widya; Karja, Ni Wayan Kurniani (Jurnal Veteriner, 2015)
The aim of the present study was to investigate the characteristics of frozen-thawed Garut ramsemen when cryopreserved in extender supplemented with Orvus Es Paste (OEP) as surfactant. Ramsemen were collected and evaluated, then cryopreserved in extender supplemented with OEP at differentconcentrations: OEP-0 (without OEP); OEP-0.25%; OEP-0.50%; OEP-0.75%; and OEP-1.00%. Thecharacteristics observed were motility, viability, and Intact Plasma Membrane (IPM). The results showedthat semen which were cryopreserved and supplemented with OEP had a higher motility, viability, andIPM, respectively compared to those without OEP. No significant differences in the characteristics wereobserved within the different OEP concentrations. It can be concluded that supplementation of OEP in theextender could protect the quality of cryopreserved ram spermatozoa.
Keywords: Orvus Es Paste, frozen-thawed, surfactant, spermatozoa, goat